Peran Guru dalam Keberhasilan Implementasi Kurikulum 2004 - - Suwarno (Jurnal Ekonomi dan Pendidikan, 2005)
Teacher is important factor that may affect success of 2004 curriculum implementation. Based on implementation of 2004 curriculum, teacher quality can be examined from two aspects. From process aspect, a teacher is categorized success if he or she is able to actively involve most of his or her students in learning process. From result aspect, a teacher is categorized success if learning process can alter most of students attitude. It is necessary for teacher to understand that all students are endowed with high curiosity. They have potency to fulfill their curiosity, therefore the main teacher duty is how to create and maintain a comfortable learning atmosphere in order to stimulate student curiosity, and hence occur motivation and spirit to learn.